Internalisasi Nilai dan Karakter Melalui Budaya Sekolah Dengan Kegiatan Jumat Bersih di SMAN 8 Bekasi - Farida Fitria; Yayat Suharyat (Universitas 45 Surabaya, 2022)
This study reviews the objectives of the Clean Friday program concept and its application as a vehicle to deliver student character improvement in the school environment, especially in terms of character. The subjects of this study were students of SMA Negeri 8 Bekasi. The research data was taken from the results of observations, observations, and interviews with several parties. The method in this study uses descriptive qualitative. Character is something that is attached to a person to shape his personality. This study describes the results, namely showing that the Clean Friday program can foster creativity, religious values, nationalism, the value of love for cleanliness and the environment, the value of cooperation, the value of responsibility, and the value of care for the environment, as well as an attitude of helping each other. Therefore, this program is a recommendation for educational institutions to develop and implement the Clean Friday program to become a flagship program in the school environment